A ética prática no pensamento de Peter Singer - Virgínio, Sérgio Ricardo de Andrade (2011)
This study was to analyze the guiding utilitarian ethics, from his contributions regarding the applicability of its proposals in time. So we try to bring, from the search of the precursors of utilitarianism, how, when, and under what conditions is epochal discussions that have brought into question the possibility of consolidation and transformation of such a debate in moral theory. Thus we can see better the importance of utilitarian theory in our capitalist tradition, which underlies our relations in the world today. This importance of the utilitarian tradition in relation to moral philosophy, appears in the contemporary world, the figure of Peter Singer, who with his utilitarian approach replaces the debate about the so-called moral values, proposing to review the whole concept of ethics and agree to put our days as a condition essential to building a better world for future generations. We have analyzed the practical ethics of Peter Singer, from his own work, in order to work more closely your own text, since the very Singer argues that criticism to his propositions, in most cases occurs by a cursory reading of his work. Thus, we see more clearly the importance of analyzing the best philosophy of that author, as an opportunity unquestionable break old paradigms and move in-depth discussions and and at the same time, innovative, relevant and constructive views of the world more open and, therefore generating less pain and more happiness.